The Knowledge and Attitude of Married men towards the use of Vasectomy as a Means of Family Planing in a Nigerian University - Esievo, Judith Njideka; Isioma Jane, Onwuegbute; Favour, Obehi; Falade, Oladimeji Joshua; Raphael, Oladimeji Ojo (Journal of Neonatal Surgery, 2025)
Introduction: Vasectomy is an effective family planning option. However, the patriarchy entrenched in African and developing countries contributes to its limited adoption. Additionally, the centralization of family planning services since their inception has made it difficult for men to embrace family planning options. Aim: This study aimed to assess the level of knowledge about vasectomy among married men at Delta State University, Abraka, Nigeria. It also sought to determine their attitudes towards the use of the procedure. Methods: A descriptive research design was utilized for this study. A purposive sampling technique was employed to select 164 respondents. A researcher-administered semi-structured questionnaire was used for data collection. Results: The findings indicated that respondents had a good understanding of vasectomy but held a negative attitude toward its use. Out of 164 respondents, 97.0% understood its purpose. However, 81.1% of them are unaware that the procedure can be reversed. With regards to attitude, they had negative attitude towards vasectomy as 87.2% of the respondents were of the view that vasectomy was not accepted in the society, and only 38.4% are of the opinion that family planning was a shared responsibility between them and their wife. Conclusion: Despite the high level of awareness this study highlights a notable gap in attitude regarding the use of the procedure. Concerns raised from feedback generated from response to attitudinal statements shows that there is a negative perspective and opinion about the procedure due to unacceptability in the society. Encouraging family planning initiatives for men is essential particularly within the context of Nigeria’s patriarchal social structures. Health education and outreach programs are effective strategies for dispelling misconceptions and addressing concerns that may contribute to negative attitudes among men.